Critical Discourse Analysis on Representation of Arab Spring in the Movie Alephia 2053 - Rarasati, Indah; Zawawi, Mohammad (Bina Nusantara University, 2024)
The research aimed to find out the representation of the Arab Spring and described the forms of social dimensions in the movie entitled Alephia 2053. It a movie telling the story of an Arab country in the future that still adhered to a monarchical system of government. The story in Alephia 2053 had similarities to events in Arab countries. The reality was the chaos that occurred in Arab countries a few years ago, known as the Arab Spring. The research was designed applying a descriptive qualitative research method with Norman Fairclough’s critical discourse analysis approach. The data analysis technique used was to analyze the data descriptively using Norman Fairclough’s perspective of Critical Discourse Analysis theory. The research finding reveals that the Arab Spring’s representation in the movie Alephia 2053 is in the form of a government coup and the democracy slogan action. The finding also indicates social dimensions as (a) in the text dimension, eleven words are fought for and contain forms of representation, relationships, and identity; (b) in discursive practice, three data contents support evidence of the ideological words; (c) in sociocultural practices, there are relations, social, and cultural processes in the form of information, in the form of binary opposition between the regime, state officials and the people which describes three levels of sociocultural practices, namely situational, institutional, and social levels.